Changing Dynamics of Arab Rule in Multan from the Eighth to Eleventh Centuries CE: A Study of the Banū Sāmah Kingdom - Shaheen, Mehnaz; Ahmed, Fouzia Farooq (Islamic Studies, 2023)
This article studies the political, social, and economic patterns of Multan under Arab rule based on both primary and secondary sources. The mercantile cosmopolis Multan remained at the periphery of the central Muslim empires and had a heterogenous population with orthodox and heterodox tendencies. The rulers of these regions realized that their political power dynamics could not be like those of the centre because of their mercantile and pilgrim economy. Under the Banū Sāmah, the emirs of Multan followed a metadoxy, pietistic, and mercantile cosmopolitanism policy, as the state measures for the imposition of orthodoxy and the control of the belief system were lax. Nevertheless, the Fatimids destroyed the Aditya Sun Temple, though they signed a truce with Hindu kingdoms of surrounding areas against Maḥmūd of Ghazni without foreseeing its consequences. Multan’s political and religious dynamics in the medieval era were intricately intertwined with the political, moral, and financial economy as the economic, political, and multicultural religious dynamics were in deep nexus.